The Role of Embeddedness of Migrant Start-ups in Local Entrepreneurial Ecosystems During the COVID-19 Crisis - Terstriep, Judith; David, Alexandra; Ruthemeier, Alexander; Elo, Maria (Journal of Comparative International Management, 2023)
As with all start-ups, the COVID-19 pandemic has led to a changing environment for migrant start-ups. These changes have posed many challenges to altering strategic behaviour and approaches to driving business. We explored migrant start-ups’ embeddedness in entrepreneurial ecosystems by analysing data from 14 semi-structured interviews with start-ups from Berlin's knowledge-intensive business services sector. We argue that the success of migrant start-ups during crises is dependent mainly on the embeddedness in the local entrepreneurial ecosystem. Thus, we expect entrepreneurs to utilise local networks, infrastructures and interactions to help them cope with the challenges and pave the way for local and international business activities. Our results indicate that embedding in local entrepreneurial ecosystems and a sense of belonging, especially during the business formation phase, play a vital role for migrant start-ups in general and crisis. Revitalising the concept of local embeddedness while considering business development stages, this study challenges the prevailing notion of transnational networks as the sole determinant of entrepreneurial success. Instead, we advocate for greater recognition of the significance of accessing local resources, including market knowledge, social relationships, and institutional support, as fundamental factors driving business development and crisis management within the host country. By recognising and nurturing these local resources, policymakers and support organisations can create an enabling environment that empowers migrant start-ups to thrive, adapt, and contribute to the local EE and economic wealth.